2015
DOI: 10.1039/c4md00566j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of anticancer activity of novel andrographolide derivatives

Abstract: A series of 3,19-O-acetal derivatives of andrographolide (1) have been synthesized by protecting the hydroxyls at C-3 and C-19 through a novel route. All the derivatives were evaluated for in vitro anticancer activity. Among the synthesized derivatives, compounds 3, 3a, 3d, 3e, 7 and 8 showed potential cytotoxicity against human cancer cell lines A549 (lung), HeLa (cervical), ACHN (renal), B-16 (melanoma) and IEC-6 (small intestine). The binding mode conformation was evaluated through docking simulations, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 41 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, for the purpose of understanding the effects of electron-withdrawing and electron-donating groups, different thioether andrographolide derivatives substituted with fluorobenzene, nitrobenzene, methylbenzene, and methoxylbenzene were synthesized using the same strategy. The removal of the isopropylidene group of I (1-9) was carried out by employing AcOH/H 2 O to readily furnish the target compounds II (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Chemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, for the purpose of understanding the effects of electron-withdrawing and electron-donating groups, different thioether andrographolide derivatives substituted with fluorobenzene, nitrobenzene, methylbenzene, and methoxylbenzene were synthesized using the same strategy. The removal of the isopropylidene group of I (1-9) was carried out by employing AcOH/H 2 O to readily furnish the target compounds II (10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Chemistrymentioning
confidence: 99%
“…In recent years, scientists have revealed that andrographolide and its derivatives possess anticancer activity both in vitro and in vivo. 2,[11][12][13][14][15][16][17][18][19] The mechanism of the antitumor actions is mainly through induction of cell cycle arrest and promotion of apoptosis in human cancer cells by attenuating various cell signaling pathways. [12][13][14] A series of andrographolide derivatives has been previously synthesized to screen their in vitro cytotoxicity against cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our earlier studies on the cyclic acetal protection of hydroxyls of forskolins and andrographolides with suitable functional groups, significantly increased its cytotoxicity [41][42][43]. In view of the above finding, it is envisaged that synthesis of a hybrid of forskolin-indole-1,2,3triazole (FIT) and its anlogues may result in high value, potent, selective and less toxic bioactive molecules.…”
Section: Introductionmentioning
confidence: 99%